An investigation into adjunct used in the textbook solutions (elementary and pre-intermediate) by tim falla, paul a davies - Phạm,Thị Hoài; Trần Quảng Hải (ĐHĐN : ĐHĐN., 2015)
This research paper deals with the linguistic features of the adverbial adjuncts in the texts of English in general and in the textbook Solutions in particular in terms of syntax, semantics. On the base of the statistics and analysis, the study aims at presenting the commonly used syntactic structures as well as the semantic features in the texts of adjuncts in English. In this thesis the author tried to distinguish adjunct from disjunct and conjunct as well as paid much attention to the semantic classification of adverbials. She also analysed the adjunct adverbials in English from collected data into three positions in the clause: initial, medial and end. The author hopes that from the results of the research, some interpretations can be applied in teaching and learning English and this can help learners understand or use “the peripheral part” of the sentence more easily and successfully.
Keywords: adjunct used in the textbook solutions; adjunct -- adjunct used in the textbook